Analysis of the Financial Statements of the Binjai City Pamong Praja Police Unit Cooperative 2023 - Mariani, Dewi Sartika; Waqqosh, Abi (Doktor Ilmu Manajemen, Universitas Muslim Indonesia, 2025)
This study analyzes the financial performance of the Binjai City Satpol PP Cooperative in 2023 using liquidity, solvency, and profitability ratios. The liquidity ratio is measured using the Current Ratio, which shows a value of 2. This figure indicates that the cooperative has a good ability to meet its short-term obligations, where every Rp.1 liability is supported by Rp.2 current assets. Solvency analysis using Debt to Equity Ratio shows a value of 0.67, which means that equity is greater than total liabilities. This ratio reflects a healthy capital structure with relatively low financial risk. Meanwhile, the profitability analysis measured by Return on Assets (ROA) shows a value of 12%. This shows that the cooperative is able to generate a profit of Rp.0.12 for every Rp1 of assets it owns, which reflects efficiency in asset management. The financial performance of the Binjai City Satpol PP Cooperative is classified as healthy with good liquidity, low solvency level, and fairly high profitability. However, to improve competitiveness and business sustainability, the cooperative is advised to diversify its business to reduce dependence on one source of income. In addition, receivables management needs to be improved by implementing stricter credit policies and more effective collections to keep cash flow healthy. With these strategic measures, the cooperative can maintain its financial stability and improve the welfare of members in a sustainable manner.